2013
DOI: 10.4236/ijg.2013.45b008
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Dissolved Oxygen with Chlorophyll-a and Phytoplankton Composition in Tilapia Ponds

Abstract: This study investigated the relationships among the parameters of dissolved oxygen, chlorophyll-a and phytoplankton composition in tilapia ponds. Each pond (a total of 18 ponds) was sampled once in the dry, winter season between January and March and again early in the rainy season between May and June. The data were analyzed by examining correlations among parameters as affected by season, altitude and culture system. Observations were made at sites located in 5 selected provinces of northern Thailand: Chiang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 9 publications
(10 reference statements)
2
18
0
Order By: Relevance
“…Oxygen super saturation (values > 120%), can indicate elevated phytoplankton photosynthesis and this is confirmed by the abundant presence of PK (data not showed) observed during this seasons (28,29). DO shows a significant negative correlation with pH (P<0.001), that should be in part confirmed by Frieder et al (2012) (30), in case of high values of DO, and also with Chl-a (P<0.001), as also reported by Kunlasak et al (2013) (31). Concentrations of salt nutrients and Chl-a are summarized in Tables 1A and B and reported as graph in Figure 4, with median, 25% and 75% percentile, maximum and minimum highlighted.…”
Section: Resultssupporting
confidence: 79%
“…Oxygen super saturation (values > 120%), can indicate elevated phytoplankton photosynthesis and this is confirmed by the abundant presence of PK (data not showed) observed during this seasons (28,29). DO shows a significant negative correlation with pH (P<0.001), that should be in part confirmed by Frieder et al (2012) (30), in case of high values of DO, and also with Chl-a (P<0.001), as also reported by Kunlasak et al (2013) (31). Concentrations of salt nutrients and Chl-a are summarized in Tables 1A and B and reported as graph in Figure 4, with median, 25% and 75% percentile, maximum and minimum highlighted.…”
Section: Resultssupporting
confidence: 79%
“…The recorded decrease of oxygen concentration during treatment with alum compared with control is attributed to the decrease in phytoplankton growth. As dissolved oxygen saturation point is 8.5 mg L −1 at 25°C, the increase in dissolved oxygen recorded in Table 3 confirms that the dissolved oxygen was affected not only by algal photosynthesis but also by aquatic respiration, oxidative decomposition of settled organic compounds such as nutrients, fish, and animal wastes (Kunlasak et al 2013). Koohestanian et al (2008) stated that 85-98 % reduction of water turbidity can be achieved using the optimum coagulant dosage (8 mg L −1 ferric chloride and 10 mg L −1 alum) in the optimum pH range (9.2 for ferric chloride and 8.5 for alum) which is in agreement to the present results.…”
Section: Discussionsupporting
confidence: 69%
“…Chlorophyll-a concentration above 0.2 mg m À3 is good enough to increase planktonic activity which ultimately assists in improving fish activity (Zainuddin et al 2004). Study on levels of chlorophyll-a in tilapia pond revealed that, an increase in plankton high in chlorophyll-a yields a higher concentration of dissolved oxygen (Kunlasak et al 2013). Chlorin and phytol are metabolites of chlorophyll and are reported to have antioxidant and anticarcinogenic effect in various kinds of marine fish, with phytol as an essential nutrient that regulates cellular metabolism (Ma & Dolphin 1999).…”
Section: Chlorophyll-a and Bmentioning
confidence: 99%